1997
DOI: 10.1046/j.1365-2141.1997.2993116.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to CD44 enhance adhesion of normal CD34+ cells and acute myeloblastic but not lymphoblastic leukaemia cells to bone marrow stroma

Abstract: Summary. The role of CD44 in the adhesion of haemopoietic cells to bone marrow stromal layers has not been clearly defined in humans, although its importance in the murine system has been well documented. We have demonstrated that the CD44 antibody, NIH44-1, enhances the adhesion of haemopoietic cells to bone marrow stroma. Normal human CD34 þ haemopoietic progenitors and blasts from patients with acute myeloblastic, but not lymphoblastic, leukaemia responded to NIH44-1. All CD44 antibodies tested which bound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…Our results have demonstrated that CD44 is involved in cell adhesion of the KG1a cells and of CD34+ HPC and confirmed that CD44 is localized on the uropod of CD34+ cells at the site of contact in alignment with previous studies [Giebel et al, 2004;Wagner et al, 2005a]. Other authors demonstrated that CD44 plays a major role in HPC stroma adhesion in the murine [Miyake et al, 1990] and human system [Bendall et al, 1997;Bendall and Gottlieb, 1999;Muller-Sieburg et al, 2000]. CD44 has at least 3 nonoverlapping epitopes.…”
Section: Discussionsupporting
confidence: 77%
“…Our results have demonstrated that CD44 is involved in cell adhesion of the KG1a cells and of CD34+ HPC and confirmed that CD44 is localized on the uropod of CD34+ cells at the site of contact in alignment with previous studies [Giebel et al, 2004;Wagner et al, 2005a]. Other authors demonstrated that CD44 plays a major role in HPC stroma adhesion in the murine [Miyake et al, 1990] and human system [Bendall et al, 1997;Bendall and Gottlieb, 1999;Muller-Sieburg et al, 2000]. CD44 has at least 3 nonoverlapping epitopes.…”
Section: Discussionsupporting
confidence: 77%
“…Instead one of the antibodies even adhesion appears counter-intuitive, it is not unprecedented. Oostendorp et al (Oostendorp et al, 1996;Bendall et al, 1997) showed after testing a panel of nineteen anti-CD44 antibodies, that while none of them blocked hematopoietic cells from adhering to bone marrow stroma, nine of them actually enhanced binding. The majority of those that did were antibodies directed to epitope 1 of CD44, which is also the epitope recognized by the CD44 antibody (antibody 3) that exhibited the greatest enhancement of monocyte adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining chemotactic activity after digestion of synthetic human CXCL12α was measured using CD34 + cells freshly isolated from normal human BM (26) or Nalm-6 cells as previously described (27). Cells (5 × 10 4 ) were plated in 8-µm pore transwell inserts (Corning Costar, Cambridge, Massachusetts, USA).…”
Section: Mobilization Of Human Patients and Donorsmentioning
confidence: 99%